The Sacred in Contemporary Advertising - Cătălin Soreanu (Anastasis: Research in Medieval Culture and Art, 2016)
As part of the contemporary media culture, advertising constantly mediates the relationship between the institutional dimension of religion (namely the church) and the community, given the specific position of the Catholic religion: transparent, based on dialogue and the continuous questioning of the relationship between man and divinity. To manage their presence in public life, the church constantly approaches new media and specific forms of communication (posters, street banners and meshes, websites or interactive mobile structures).